Molecular characterisation and expression analysis of scavenger receptor class B member 1 (SR-B1) gene in Nile tilapia Oreochromis niloticus (Linnaeus, 1758) - Huang, Yucong; Cai, Shuanghu (Indian Journal of Fisheries, 2019)
The scavenger receptor class B member 1 (SR-B1) plays an important role in the first level of host defense against invading pathogens. In the present study, we cloned and characterized SR-B1 gene from Oreochromis niloticus (Linnaeus, 1758). The sequence of SR-B1 is 2248-bp long and contains a 1404-bp ORF encoded 467 amino acids. The sequence alignment showed that SR-B1 gene contains ten exons and nine introns. A multiple alignment analysis suggested that SR-B1 protein contains the conserved CXXS redox and GXXXG motifs, and shared high similarities with that of other species. On a phylogenetic tree, SR-B1 clustered with those of other teleosts and formed a separate fish clade. Real-time quantitative PCR analysis showed that SR-B1 was differentially expressed in various tissues and the expression levels in spleen and intestine were significantly upregulated by Streptococcus agalactiae infection. The results suggest that SR-B1 may be involved in the immune response against bacteria in Nile tilapia.Keywords: Gene expression, Oreochromis niloticus, SR-B1, Streptococcus agalactiae, ,Phylogenetic analysis